Multi-objective optimization in service systems - Gonsalves, T.; Yamagishi, K.; Itoh, K. (Journal of Digital Information Management, 2010)
Muti-objective optimization deals with the simultaneous optimization of two or more conficting objective functions in real-life systems. This paper deals with the multi-objective optimization in service systems. The goal of service systems is to provide cost-efficient service to customers, while at the same time, reducing the customer waiting time for service. In general, a low cost in system operation leads to longer waiting times, while a higher cost in system operation leads to shorter waiting times. The two objectives - service cost (operational cost) and waiting time (customer satisfaction) are, therefore, conficting in nature. We use the novel Multi-Objective Particle Swarm Optimization (MOPSO) algorithm to optimize the two conficting objective functions simultaneously. MOPSO is a fairly recent swarm intelligence meta-heuristic algorithm known for its simplicity in programming and its rapid convergence. The multi-objective optimization procedure is illustrated with the example of a practical service system. MOPSO produces a family of well-spread Pareto fronts for the two objective functions in the practical service system.
Keywords: Multi-Objective Particle Swarm Optimization; Service cost; Service systems; Simulation optimization